2021
DOI: 10.4414/smw.2021.20517
|View full text |Cite
|
Sign up to set email alerts
|

NRS-2002 components, nutritional score and severity of disease score, and their association with hospital length of stay and mortality

Abstract: BACKGROUND: Malnutrition is a substantial issue in hospitals, leading to prolonged length of hospital stay, increased perioperative morbidity and increased mortality. There are several validated screening tools for malnutrition, one of which is the Nutritional Risk Screening 2002 (NRS). It screens patients based on recent weight loss, reduction of recent food intake, body mass index (BMI), severity of disease and age. Higher NRS scores have been shown to be negatively associated with patients' outcomes such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 22 publications
1
11
0
4
Order By: Relevance
“…As we have published previously, specific antibiotic-related variables (duration of systemic therapy, administration by the intravenous route) were not associated with the overall risk of clinical failure in these multifaceted DFI populations [ 2 , 3 , 10 ]. Our results confirm those of previous studies in other fields of medicine that have shown that a higher NRS-Score can be associated with a longer hospital stay [ 7 ]. Importantly in this regard is that we also found that providing nutritional interventions may decrease the duration of hospitalization.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…As we have published previously, specific antibiotic-related variables (duration of systemic therapy, administration by the intravenous route) were not associated with the overall risk of clinical failure in these multifaceted DFI populations [ 2 , 3 , 10 ]. Our results confirm those of previous studies in other fields of medicine that have shown that a higher NRS-Score can be associated with a longer hospital stay [ 7 ]. Importantly in this regard is that we also found that providing nutritional interventions may decrease the duration of hospitalization.…”
Section: Discussionsupporting
confidence: 92%
“…We used a DFI registry that we developed, which lists all episodes occurring since the year 2000 [ 6 ]. One author (VT) completed the registry for his master degree, with five additional variables: an internationally validated nutrition score [ 7 ], a history of involuntary weight loss, treatment with vitamin substitutions or other nutritional interventions by our professional nutritionists, and the serum albumin level on admission (if available). Since 2003, we used the standardized NRS-Score (Nutritional Risk Screening Score 2002, with a range of 0 to 7) [ 7 ] throughout the study period.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We set 2 as the cut-off value for CONUT score by a receiver operating characteristics (ROC) curves analysis (online Supplementary Fig. S1) and categorised the patients into low-CONUT and high-CONUT groups according to the CONUT score: no or low risk of malnutrition (0-1) and high malnutrition risk (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). The NRS-2002 score of ≥ 3 points indicates that the patient is at nutritional risk (23) , considering the impaired nutritional status, the severity of the disease and the patients' age.…”
Section: Controlling Nutritional Status Score and Nutritional Risk Sc...mentioning
confidence: 99%
“…Several quantitative tools with scoring scales have been developed to assess nutritional risk, postoperative complications and long-term outcomes, such as the prognostic nutritional index and Nutritional Risk Screening index (NRS-2002) (8,9) . NRS-2002, as a standard method to assess nutritional risk, has been validated and conducted in hundreds of reported studies (10,11) . Controlling nutritional status (CONUT) is a newly proposed screening tool for assessing nutritional status and has been validated in several clinical settings (12,13) .…”
mentioning
confidence: 99%